An Evaluation of the Effect of a One or Two-Step Gestational Diabetes Mellitus Screening Program on Obstetric and Neonatal Outcomes in Pregnancies - Akgol, Sedat; Obut, Mehmet; Baglı, İhsan and Kahveci, Bekir and Budak, Mehmet Sukru (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objectives: The aim of this study was to compare the obstetric and neonatal outcomes of pregnant women who were screened with one or two-step screening programs for diagnosis of gestational diabetes mellitus. Study Design: A retrospective evaluation was made of pregnant women who were screened with one step [75 g oral glucose tolerance test] or two-step screening programs [50 g oral glucose challenge test and 100 g oral glucose tolerance test] depending on the preference of the physician between September 2016 and August 2017. Results: The one-step screening program was applied to 34.1% (n:1358) of the pregnancies and the remaining 65.9% (n=2623) were screened using the two-step program. The following results were obtained for the pregnant women applied with the one and two-step screening programs, respectively; mean age: 29.37±7.6 years and 28.1 ± 6.2 years, gestational diabetes mellitus: 8.8% and 4.8%, pre-term birth:5.2% and 6.9%, term birth: 89.8% and 85.5%, post-term birth: 5% and 7.6%, vaginal delivery: 74.8% and 67.5%, caesarean section delivery: 25.2% and 32.5%, birth weight: 3389±432 gr and 3234.1 ± 415.9 gr, and mean 5-minute APGAR score: 9.1 ± 0.4 and 9.2 ± 0.7. Comparisons showed statistically significant differences between the groups. Conclusion: The study results showed a significantly higher rate of gestational diabetes mellitus diagnosis for the pregnant women screened with the one-step screening program than the two-step screening program. Although the mean maternal age was significantly higher in the pregnant women screened with the one-step screening program, these pregnancies were observed to have better outcomes (low rates of preterm birth, post-term birth, caesarean delivery and high rates of term birth, vaginal delivery). These results can be attributed to the early referral to a treatment program and follow-up, even though more cases of gestational diabetes mellitus were diagnosed with the one-step screening program.